Extracellular vesicular microRNAs and cardiac hypertrophy - Hu, Hai; Wang, Xiulian; Yu, Hui; Wang, Zhanli (Frontiers in Endocrinology, 2025)
Cardiac hypertrophy is an adaptive response to pressure or volume overload such as hypertension and ischemic heart diseases. Sustained cardiac hypertrophy eventually leads to heart failure. The pathophysiological alterations of hypertrophy are complex, involving both cellular and molecular systems. Understanding the molecular events that inhibit or repress cardiac hypertrophy may help identify novel therapeutic strategies. Increasing evidence has indicated that extracellular vesicle (EV)-derived microRNAs (miRNAs) play a significant role in the development and progression of cardiac hypertrophy. In this review, we briefly review recent advancements in EV research, especially on biogenesis, cargoes and its role in cardiac hypertrophy. We then describe the latest findings regarding EV-derived miRNAs, highlighting their functions and regulatory mechanisms in cardiac hypertrophy. Finally, the potential role of EV-derived miRNAs as targets in the diagnosis and treatment of cardiac hypertrophy will be discussed.